2017
DOI: 10.1002/lno.10547
|View full text |Cite
|
Sign up to set email alerts
|

Thaumarchaeal ecotype distributions across the equatorial Pacific Ocean and their potential roles in nitrification and sinking flux attenuation

Abstract: Thaumarchaea are among the most abundant microbial groups in the ocean, but controls on their abundance and the distribution and metabolic potential of different subpopulations are poorly constrained. Here, two ecotypes of ammonia-oxidizing thaumarchaea were quantified using ammonia monooxygenase (amoA) genes across the equatorial Pacific Ocean. The shallow, or water column "A" (WCA), ecotype was the most abundant ecotype at the depths of maximum nitrification rates, and its abundance correlated with other bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
105
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(138 citation statements)
references
References 94 publications
(139 reference statements)
31
105
1
1
Order By: Relevance
“…Spatial trends in the normalized abundances of thaumarchaeal rpoB , amoA and nirK suggested an increasing numerical dominance of Thaumarchaeota with depth (Fig. ), in agreement with numerous surveys in marine systems previously (e.g., Santoro et al ., ; Müller et al ., ). At both stations, abundances of the three genes were highest in the upper mesopelagic depths (80 and 100 m) as well as at 500 m. In contrast, the shallow euphotic depths (i.e., 30 m at M1 and 40 m at M2) had substantially lower abundances of the three genes (<2% of the total community).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Spatial trends in the normalized abundances of thaumarchaeal rpoB , amoA and nirK suggested an increasing numerical dominance of Thaumarchaeota with depth (Fig. ), in agreement with numerous surveys in marine systems previously (e.g., Santoro et al ., ; Müller et al ., ). At both stations, abundances of the three genes were highest in the upper mesopelagic depths (80 and 100 m) as well as at 500 m. In contrast, the shallow euphotic depths (i.e., 30 m at M1 and 40 m at M2) had substantially lower abundances of the three genes (<2% of the total community).…”
Section: Resultsmentioning
confidence: 97%
“…Vertical niche partitioning between thaumarchaeal ecotypes has been evident in qPCR abundances of amoA variants (Beman et al, 2008;Santoro et al, 2010;Smith et al, 2014;Sintes et al, 2016;Smith et al, 2016;Santoro et al, 2017;Müller et al, 2018). Inferring these differential distribution patterns based on nirK abundances, however, had not been attempted so far.…”
Section: Assessing Microdiversity Within Thaumarchaeal Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two ecotypes exist within the Thaumarchaeal nitrifying clade whose identity can be distinguished by their ammonia monooxygenase gene ( amoA ) sequence (Francis et al ., ). These two ecotypes exhibit different niche preferences and unique functional roles in the ocean (Santoro et al ., ). Further research is required to identify whether 16S rRNA phylogeny is sufficient to describe the ecophysiology of the other Archaea identified in our study and, thus, may explain why differentiation among clades between size fractions is not evident.…”
Section: Discussionmentioning
confidence: 97%
“…Since the first phylogenetic analysis of AOA amoA gene in the ocean (Francis et al, 2005), two groups, water column A (WCA) and water column B (WCB), were reported as the major groups of AOA in the oceanic waters, and they were proposed as two ecotypes predominating in upper (<200 m) and deep (>200 m) layers, respectively (Beman et al, 2008;Francis et al, 2005;Santoro et al, 2017). So far, there is only one culture of WCA (Nitrosopelagicus brevis CN25) reported (Santoro & Santoro & Casciotti, 2011;Santoro et al, 2015) and the WCB is still uncultivated; therefore, the physiology of these two ecotypes is still unclear (Santoro et al, 2017). In spite of this unclearness, several factors have been hypothesized as potentially causing the vertical succession of WCA and WCB, including light inhibition, differential affinities and utilization of nitrogen sources, and different requirements of micronutrients (Amin et al, 2013;Luo et al, 2014;Qin et al, 2014;Santoro et al, 2017;Sintes et al, 2013Sintes et al, , 2016Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%